The crooked staircase ebook - Koontz, Dean (Jane Hawk, 2018)
NEW YORK TIMES  BESTSELLER • Jane Hawk—who dazzled readers in The Silent Corner and The Whispering Room —faces the fight of her life, against the threat of a lifetime, in this electrifying thriller by #1  New York Times bestselling suspense master Dean Koontz.   “I could be dead tomorrow. Or something worse than dead.”   Jane Hawk knows she may be living on borrowed time. But as long as she’s breathing, she’ll never cease her one-woman war against the terrifying conspiracy that threatens the freedom—and free will—of millions. Battling the strange epidemic of murder-suicides that claimed Jane’s husband, and is escalating across the country, has made the rogue FBI agent a wanted fugitive, relentlessly hunted not only by the government but by the secret cabal behind the plot. Deploying every resource their malign nexus of power and technology commands, Jane’s enemies are determined to see her dead . . . or make her wish she was. Jane’s ruthless pursuers can’t stop her from drawing a bead on her prey: a cunning man with connections in high places, a twisted soul of unspeakable depths with an army of professional killers on call. Propelled by her righteous fury and implacable insistence on justice, Jane will make her way from southern Southern California to the snow-swept slopes of Lake Tahoe to confront head-on the lethal forces arrayed against her. But nothing can prepare her for the chilling truth that awaits when she descends the crooked staircase to the dark and dreadful place where her long nightmare was born. Don’t miss any of Dean Koontz’s gripping Jane Hawk thrillers: THE SILENT CORNER • THE WHISPERING ROOM • THE CROOKED STAIRCASE • THE FORBIDDEN DOOR  • THE NIGHT WINDOW  Praise for The Crooked Staircase “An absorbing thriller full of fresh touches . . . Writing his unusual heroine, Koontz keeps the pages alive with attitude as well as action. . . . For Hawk, who is as fearless as she is beautiful, no obstacle is too great, especially with the well-being of her hidden-away five-year-old son on her mind.” — Kirkus Reviews “Spellbinding . . . Beautifully plotted and written with notable care and flare . . . The Hawk series . . . is among [Koontz’s] best work.” —Booklist (starred review) “Unrelenting . . . [Jane] rivets readers’ attention. . . . Michael Crichton fans and thriller aficionados who appreciate a fierce female protagonist . . . should be urged to meet Jane Hawk.” — Library Journal